Higgs-Yukawa Model in Chirally Invariant Lattice Field Theory - John Bulava; Philipp Gerhold; Karl Jansen; Jim Kallarackal; Bastian Knippschild; C.-J. David Lin; Kei-Ichi Nagai; Attila Nagy; Kenji Ogawa (Advances in High Energy Physics)
Nonperturbative numerical lattice studies of the Higgs-Yukawa sector of the standard model with exact chiral symmetry are reviewed. In particular, we discuss bounds on the Higgs boson mass at the standard model top quark mass and in the presence of heavy fermions. We present a comprehensive study of the phase structure of the theory at weak and very strong values of the Yukawa coupling as well as at nonzero temperature.